2018
DOI: 10.1556/2006.7.2018.69
|View full text |Cite
|
Sign up to set email alerts
|

Online social networking addiction and depression: The results from a large-scale prospective cohort study in Chinese adolescents

Abstract: Background and aimsThe aim of this study is to estimate the longitudinal associations between online social networking addiction (OSNA) and depression, whether OSNA predicts development of depression, and reversely, whether depression predicts development of OSNA.MethodsA total of 5,365 students from nine secondary schools in Guangzhou, Southern China were surveyed at baseline in March 2014, and followed up 9 months later. Level of OSNA and depression were measured using the validated OSNA scale and CES-D, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 46 publications
5
65
3
6
Order By: Relevance
“…A growing body of evidence suggest that there is a bidirectional relationship between problematic social media use and psychopathological variables (Li et al 2018). Individuals become problematic users in attempts to cope with their real-life troubles and/or escape from their reality (Kircaburun and Griffiths 2018).…”
Section: Problematic Instagram Use and Psychopathological Outcomesmentioning
confidence: 99%
“…A growing body of evidence suggest that there is a bidirectional relationship between problematic social media use and psychopathological variables (Li et al 2018). Individuals become problematic users in attempts to cope with their real-life troubles and/or escape from their reality (Kircaburun and Griffiths 2018).…”
Section: Problematic Instagram Use and Psychopathological Outcomesmentioning
confidence: 99%
“…Mechanisms in this potential reverse causality can include cognitive− and affective−related maladaptive coping strategies such as repetitive negative thinking and emotion dysregulation [39]. The bidirectional association was hence possible and evident by the reciprocal relations found in prospective cohort studies in young people [7,40].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Chinese scholars recently conducted one longitudinal study where they focused on middle school adolescents. The study conducted in Guangzhou included 5,365 students, with 735 that were reported with depression at baseline and 57.14 % of initially self-reported depressed participants having remained with symptoms after 9 months [12]. Admittedly, the results of the aforementioned studies provide valuable information as the majority of studies that have investigated the prevalence of persistent depression in adolescents were conducted in Western countries (e.g., USA and Europe).…”
mentioning
confidence: 99%
“…Moreover, to prevent adolescent depression at an early stage, it is essential to identify potential factors that may have contributed to depression in this age group. In particular, personal (e.g., age and gender) and familial factors were suggested to be associated with adolescent depressive symptoms including persistent depressive symptoms [12][13][14]. For instance, it was reported that adolescents were more susceptible to depression with increasing age [15], if they were biologically female, migrant students [16], had sibling(s), and/or a non-intact family (e.g., divorced families and single-parent families) [17,18].…”
mentioning
confidence: 99%